2021
DOI: 10.1007/s13721-021-00300-y
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and the digital divide as a social determinant of health during the COVID-19 pandemic

Abstract: Telehealth has been shown to have comparable health outcomes in terms of patient-physician communication, and patient satisfaction and engagement. Nevertheless, the digital divide has exacerbated the social and economic factors that create barriers to health and well-being. It, therefore, maybe a social determinant of health (SDOH). Such issues as decreased internet connectivity and a lack of Wi-Fi and video chat/webcam in both urban and rural areas can hinder the effectiveness of telehealth to its full capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 5 publications
0
69
0
1
Order By: Relevance
“…In addition to attitudes towards telehealth, social determinants may play a role in the general uptake of telehealth, and in the use of different telehealth modalities (video versus phone). Recent studies on general medical encounters during the SARS-CoV-2 pandemic have suggested differences in use of telehealth by sex, age, income, type of insurance, and race/ethnicity [11][12][13][14][15][16][17]. These studies underscore the possibility that telehealth may increase health care disparities among historically marginalized population groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to attitudes towards telehealth, social determinants may play a role in the general uptake of telehealth, and in the use of different telehealth modalities (video versus phone). Recent studies on general medical encounters during the SARS-CoV-2 pandemic have suggested differences in use of telehealth by sex, age, income, type of insurance, and race/ethnicity [11][12][13][14][15][16][17]. These studies underscore the possibility that telehealth may increase health care disparities among historically marginalized population groups.…”
Section: Introductionmentioning
confidence: 99%
“…These levels are similar to other national data which show that approximately one-fifth of all Americans may not have proper digital literacy skills [ 12 ]. We note that digital health skills may be low due to the sociodemographics associated with the veterans cared for by the VA, as it selectively cares for individuals who are older, less educated, more rural, and with lower socioeconomic status [ 13 ]—all factors known to be associated with lower digital health literacy [ 4 , 14 , 15 ]. Despite these demographic disadvantages to digital uptake, veterans who receive care in the VA appear to have more digital health skills and be more digitally prepared than veterans who do not receive care within the VA, suggesting a positive, system-level influence on these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Employing diverse recruitment methods meant that we reached out to people through email, postal mail, phone calls, and door-to-door visits to homes. This was especially important during the COVID-19 pandemic when the digital divide caused additional barriers to resources for many (11). We also offered diverse ways to participate in the study to maximize inclusivity and offset concerns about transmission risk in public spaces.…”
Section: Lesson 3: Diverse Methods Diverse Participantsmentioning
confidence: 99%